DINAMIKA KONSEP DIRI PADA EKS TAHANAN POLITIK PERISTIWA 1965 - Immanuela Senthia; Widyasoningtyas; Eka Surya (Bajang Institute, 2023)
The purpose of this research is to find out the dynamics of the self-concept of former political prisoners in the 1965 PKI event where this research uses qualitative research with interviews and literature studies from various sources which later the interview data will be triangulated by comparing from other sources. This study uses a purposive sampling technique so as to produce two sources who will be interviewed. The results of this study explain that the events of 1965 and being a political prisoner affect the dynamics of self-concept in individuals, especially the environment and self-acceptance. An environment that tends to make it difficult for individuals will build a positive self-concept and good self-acceptance will also make individuals have a positive self-concept.